Synthesis, characterization and application of zirconiamodified poly(styrene-divinyl benzene) adsorbents - Sarjadi, Mohd. Sani (2005)
Poly(styrene-divinyl benzene) (PS-DVB) resin is an attractive adsorbent for extraction and separation of various types of compounds due to its stability over the pH range of 1-14. However, PS-DVB resin is known to have hydrophobic surfaces that highly retain non-polar compounds while poorly retain polar compounds. To improve its use in the separation or extraction of polar compounds, PS-DVB resin must be chemically or physically bonded to hydrophilic groups to reduce its hydrophobic surface. This study explores the development of PS-DVB resins modified with acetyl chloride, chloroacetone and zirconyl chloride. The PS-DVB resin adsorbent was prepared by suspension polymerization method with polyvinyl alcohol as the suspension stabilizer at a stirring speed of 1000 rpm for 20 h. Modifications of the PS-DVB adsorbent were carried out via Friedel Crafts acylation reaction with acetyl chloride and chloroacetone using Lewis acid catalyst, Grignard reaction of the product with methyl magnesium chloride and reaction of the product with zirconium(IV) oxide chloride octahydrate. The products obtained were characterized using infrared spectroscopy, scanning electron microscopy, nitrogen adsorption analysis and thermal gravimetric analysis. The performance of the PSDVB- based phases was evaluated by investigating its adsorption-desorption efficiency in solid phase extraction. Comparative recovery studies showed that the pethanoyl- PS-DVB and p-2-propanoyl-PS-DVB resins were superior compared to unmodified PS-DVB and ziconia-modified PS-DVB for solid phase extraction of the test compounds 2-chlorophenol, nitrobenzene and propiophenone.